Critical Appraisal of Indices for the Assessment of Baroreflex Sensitivity - Di Rienzo, M.; Castiglioni, P.; Mancia, G.; Parati, G.; Pedotti, A. (Methods of Information in Medicine, 1997)
The sequence technique and the spectral estimation of the alpha coefficient are currently employed for the assessment of “spontaneous” baroreflex sensitivity (BRS). The comparison of performance and effectiveness of these techniques is obtained by the analysis of systolic blood pressure (SBP) and pulse interval (PI) tracings recorded in conscious cats before and after baroreceptor denervation. Results indicate that (1) the average BRS estimates obtained by the sequence technique and by the alpha coefficient at the respiratory frequency are similar, (2) the alpha coefficients computed at the respiratory frequency tend to be higher than alpha coefficients estimated at 0.1 Hz, and (3) in spite of what is traditionally claimed, the PI-SBP coherence does not seem to represent a reliable parameter to enhance the specificity of the spectral estimate, because coherence values often remain above the 0.5 threshold also after baroreceptor denervation.
Keywords: Baroreceptor Sensitivity; Arterial Blood Pressure; Heart Rate Variability